P. G. Carey, A Digest of the Ordinances of the Borough of Phoenixville, Pennsylvania 135 (1906) - (:unkn) unknown (My University, 1906)
Parks § 1.4: Prohibited carry of fire-arms, shooting birds, throwing stones or other missiles within Reeves Park.
Keywords: CARRY - CERTAIN PUBLIC PLACES; DISCHARGE